A life in common: Bodies and negotiations of public space as Common. A perspective from Dakar - Lucrezia Cippitelli (piano b)
This text proposes an anti-colonial genealogy (linked to the XX Century concepts of Pan-Africanism and Négritude) and a pre-modern genealogy (linked to ancestral cultural and existential models that have survived in post-colonial urban contexts) of contemporary participatory art experiences in the African continent. The first focus on Senegal will provide further references to festivals, biennials and triennials exhibitions and art projects on the continent. Such practices, which have entered into dialogue with the global art world through relevant international exhibitions (see, with reference to a recent example from the Global South, the Documenta curated by the Indonesian collective Ruangrupa in 2022), can be interpreted by global art critics through the lenses of hermeneutic and theoretical models proper to art-history and curatorial disciplines. However, in their complexity and hybridity - linked to the colonial history and the multicultural nature of the education of the their protagonists, artists who grew up in a dialectic between inside and outside the African continent, inside and outside the artistic education imported by the European colonies from the 19th century onwards, inside and outside their own ancestral cultures of reference – these practices must be framed in their contextual relevance and adherence, rather than within the deductive definitions of Eurocentric art criticism.